2008
DOI: 10.1097/bpo.0b013e3181651bc8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Modalities for the Evaluation of Pediatric Back Pain

Abstract: Prospective study; Level 2 clinical evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 14 publications
0
65
0
7
Order By: Relevance
“…16 For example, while some articles refer to back pain in general 11,15,17,18 others refer exclusively to low back pain 4,5,19 or to nonspecific back pain. 20,21 Back pain in children is often the manifestation of a benign process; in some cases, however, it may suggest a serious pathology such as a neoplasm or an infectious process.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…16 For example, while some articles refer to back pain in general 11,15,17,18 others refer exclusively to low back pain 4,5,19 or to nonspecific back pain. 20,21 Back pain in children is often the manifestation of a benign process; in some cases, however, it may suggest a serious pathology such as a neoplasm or an infectious process.…”
Section: Epidemiologymentioning
confidence: 99%
“…Unfortunately, organic pathology (benign or malignant) is not always identifiable; this problem, in turn, frequently leads to extensive diagnostic work-ups in children described as having nonspecific or mechanical back pain. 17,19 In a recent prospective study, Bhatia et al 17 examined the rate of pediatric back pain diagnosed and the value of the various tests used in making diagnoses. In this study, 78% of patients had no definitive final diagnosis, including those with disorders that might have been treatable but were not identified.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a specific generator of low back pain is not always found, which makes diagnosis and treatment more difficult (11). One study concluded that exhaustive diagnostic protocols may not be necessary in pediatric patients with low back pain because their symptoms do not permit a definitive diagnosis (10). However, although most cases are self-limiting, some young athletes have persistent symptoms (6).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic modalities available for evaluation of back pain in children include plain radiograph, computed tomography (CT), magnetic resonance imaging (MRI), single -photon emission CT, and laboratory investigations (10). However, a specific generator of low back pain is not always found, which makes diagnosis and treatment more difficult (11).…”
Section: Introductionmentioning
confidence: 99%